Improved Website SecurityUsing SSL and HAProxy Based PFSense Routers - Ade Frihadi; Silviana Windasari; Mardiyan Dama; Bayu Bagaskoro; Abdurohman, Abdurohman (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
Website security is a crucial aspect in the face of increasing cyber threats. This study aims to implement website protection using SSL (Secure Sockets Layer) and HAProxy (High Availability Proxy) through a PFSense router, and to evaluate its effectiveness using the securityheaders.com platform. The methodology used is an experimental study with a reverse proxy server configuration based on HAProxy and SSL certificates from Let's Encrypt. Measurement results indicate an improvement in the website's security score after the configuration was applied, particularly in security headers such as Strict-Transport-Security, X-Frame-Options, and Content-Security-Policy. This research contributes to strengthening web security architecture that is simple, efficient, and openly adoptable by government institutions and medium-scale organizations that require open-source-based security solutions.